Impact of circulating tumor DNA mutant allele fraction on prognosis in RAS‐mutant metastatic colorectal cancer. Issue 9 (31st July 2019) - Elez, Elena; Chianese, Chiara; Sanz‐García, Enrique; Martinelli, Erica; Noguerido, Alba; Mancuso, Francesco Mattia; Caratù, Ginevra; Matito, Judit; Grasselli, Julieta; Cardone, Claudia; Esposito Abate, Riziero; Martini, Giulia; et al.
Abstract : Despite major advances in the treatment of metastatic colorectal cancer (mCRC), the survival rate remains very poor. This study aims at exploring the prognostic value of RAS ‐mutant allele fraction (MAF) in plasma in mCRC. Forty‐seven plasma samples from 37 RAS ‐mutated patients with nonresectable metastases were tested for RAS in circulating tumor DNA using BEAMing before first‐ and/or second‐line treatment. RAS MAF was correlated with several clinical parameters (number of metastatic sites, hepatic volume, carcinoembryonic antigen, CA19‐9 levels, primary site location, and treatment line) and clinical outcome [progression‐free survival (PFS) and overall survival (OS)]. An independent cohort of 32 patients from the CAPRI‐GOIM trial was assessed for clinical outcome based on plasma baseline MAF. RAS MAF analysis at baseline revealed a significant correlation with longer OS [Hazard ratios (HR) = 3.514; P  = 0.00066]. Patients with lower MAF also showed a tendency to longer PFS, although not statistically significant. Multivariate analysis showed RAS MAFs as an independent prognostic factor in both OS (HR = 2.73; P  = 0.006) and first‐line PFS (HR = 3.74; P  = 0.049). Tumor response to treatment in patients with higher MAF was progression disease ( P =  0.007). Patients with low MAFs at baseline in the CAPRI‐GOIM group also showed better OS [HR = 3.84; 95% confidence intervals (CI) 1.5–9.6; P  = 0.004] and better PFS (HR = 2.5; 95% CI: 1.07–5.62; P  = 0.033). This minimally invasive test may help in adding an independent factor to better estimate outcomes before initiating treatment. Further prospective studies using MAF as a stratification factor could further validate its utility in clinical practice. Abstract : Therapy selection in first‐line treatment of metastatic colorectal cancer (mCRC) depends on tumor RAS mutation status. The use of liquid biopsy, with reported concordance rates between tissue and plasma of around 90%, is an emerging alternative to detect RAS mutations. Beyond mutation status, data support that RAS mutant allele fractions in plasma have independent prognostic value for mCRC survival.